PENGARUH PEMBERIAN KOMPOS AMPAS TAHU DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Daryadi Daryadi; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the interaction of giving the compost of tofu dregs and NPK fertilizer and to get the right dose towards the growth of cacao seedling (Theobroma cacao L.). This research was conducted by Completely Randomized Design that consists of 2 factors. The first factors is the dose of the compost of tofu dregs (K) that consists of 4 levels. The second factors is the dose of NPK fertilizer (P) that consists of 3 levels. The Parameters observed were the height of seedling, number of leaves, diameter of stem, and the width of leaves of cacao seedling.The data was analyzed by a statistic way with variance and followed by further testing Duncan’s New Multiple Range Test (DNMRT) with 5 % level. The results of this research showed. The combination of treatments of the compost of tofu dregs dose 225 g/plants and NPK fertilizer dose 2 g/plants tend to increase the growth of height of seedling, number of leaves, and diameter of stem, and the width of leaves of cacao seedling. The application of the compost of tofu dreg dose 225 g/plants have good effects toward the growth parameter of height of seedling, number of leaves, diameter of seedling stem and the width of leaves of cacao seedling. The application of NPK fertilizer dose 2 g/plants have good effects toward the growth parameter of height of seedling, number of leaves and diameter of seedling stem.Keywords: Cacao, Compost of Tofu Dregs, NPK Fertilizer